PENGARUH KOMPETENSI PEGAWAI TERHADAP KEPUASAN KERJA YANG DIMEDIASI OLEH KOMPENSASI (Influence of Employee Competence Towards Work Satisfaction Mediumed by Compensation) - Dilman Dilman; Adnan Hakim; Juharsah Juharsah (Pascasarjana Universitas Halu Oleo, 2019)
The purposes of the research are to find out (1) the effect employee competence toward compensation on Scope Dinas Pekerjaan Umum dan Penataan Ruang Wakatobi Regency, (2) the effect competence toward job satisfaction on scope Dinas Pekerjaan Umum dan Penataan Ruang Wakatobi Regency, (3) the effect compensation toward job satisfaction on scope Dinas Pekerjaan Umum dan Penataan Ruang Wakatobi Regency, (4) the effect compensation in mediating the effect employee competence toward job satisfaction on scope Dinas Pekerjaan Umum dan Penataan Ruang Wakatobi Regency. The sample taken in this study is all employees on scope Dinas Pekerjaan Umum dan Penataan Ruang Wakatobi Regency whichamounted to 38 employees. The technique of data analysis uses PLS (Partial Least Square).The result of the study showed that competence has an positive and significant effect on compensation, competence has an positive and significant effect on job satisfaction, compensation has an positive and significant effect on job satisfaction, and employee competency through compensation mediating the role of job satisfaction on Scope Dinas Pekerjaan Umum dan Penataan Ruang Wakatobi Regency.Keywords: competence, compensation, job satisfaction